The Construction of Situation Models in Narrative Comprehension: An Event-Indexing Model - Zwaan, Rolf A.; Langston, Mark C.; Graesser, Arthur C. (Psychological Science, 1995)
In this article, we propose and test a model of how readers construct representations of the situations described in simple narratives the event-indexing model According to the event-indexing model, events are the focal points of situations conveyed in narratives and are connected in memory along five dimensions time, space, protagonist, causality, and intentionality The results of a verb-clustering task provide strong support for the event-indexing model